Promoting forgiveness in cases of bullying: A review - Handayani, Arifah; Taufik; Purwandari, Eny (Universitas Mercu Buana Yogyakarta, 2024)
A systematic review on promoting forgiveness in addressing victimization analyzed 36 studies selected from 72 articles retrieved from the Scopus database spanning the years 2004 to 2023. Included articles were required to be in English, present at least an abstract, not be review articles themselves, and focus on forgiveness among victims of bullying. Critical factors influencing forgiveness identified in the literature encompass the nature of bullying, the presence of justice and punishment, empathy, timing of interventions, personal beliefs, and cognitive processes. Age-related differences also emerged as significant, necessitating tailored approaches for children, adolescents, and adults. Proposed strategies include implementing restorative justice initiatives for children, employing avoidance strategies for adolescents, and recognizing the religious dimensions for adults. Integrating forgiveness-oriented programs in educational settings, parenting practices, and workplace training is essential for shifting victims' negative perceptions toward positive outcomes. Keyword: Forgiveness; bullying; review.